The Influence of Transformational Leadership on Fostering Management Innovation in Islamic Education Institutions - Trimulyo, Joko; Lestari, Hana; Rahmawati, Ima; Thelma, Chanda Chansa (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Transformational leadership is expected to encourage positive changes and improve management quality so schools become more responsive to the demands of the times. This study aims to analyze the influence of transformational leadership on management innovation in Islamic Senior High Schools in Indonesia. Using a quantitative approach and survey design, this study involved 150 respondents, consisting of teachers and staff in selected schools. Data were collected through a structured questionnaire and analyzed using regression analysis to test the relationship between transformational leadership and management innovation. The results of the study indicate that transformational leadership has a significant influence on management innovation. School leaders who apply an inspirational leadership style have been shown to facilitate the implementation of more effective managerial practices. These findings indicate that leadership that motivates and empowers teachers and staff increases their creativity and participation in the innovation process, ultimately improving the quality of education. This study recommends developing a more effective leadership model to encourage sustainable management innovation in these schools. In addition, this study also provides important implications regarding the role of leadership in creating an environment that supports innovation in schools.